The bird community in naturally regenerating Myracrodruon urundeuva (Anacardiaceae) forest in Southeastern Brazil - Hernandes Volpato, Graziele (2013)
Conservation and restoration projects involving abandoned cattle pastures pose several challenges. Restoration ecologists recognize that natural restoration is possible, but few species can successfully colonize degraded pastures. The aim of the present study was to evaluate whether land colonized by the tree Myracrodruon urundeuva increase the amount of habitat available for bird communities in Southeastern Brazil. We used fixed point counts within a 50m radius to compare the richness and composition of the bird community inhabiting naturally regenerated M. urundeuva with that an adjacent native forest remnant and a forest restored with planted Acacia spp. We recorded a total of 68 bird species. The M. urundeuva forest was able to provide valuable habitat for bird species, including more forest species, in comparison with the Acacia planting. These results indicate that M. urundeuva is a useful species for the ecological restoration of degraded pasture land.